EFFECT OF STEVIA LEAVES CONSUMPTION ON SUGAR AND OTHER BLOOD CHARACTERS IN DIABETES-INDUCED MICE - Al-Hamdani, H. M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was designed to confirm the effect of different concentrations of water extract for stevia leaves on lowering blood sugar, cholesterol and other blood traits in diabetes-induced mice. Forty mice with weights ranging 30-35 mg per diabetic were injected intravenously into the gastric tube except for control group (non-diabetic control) and were left for one week to confirm their diabetes. The animals were divided randomly into 5 groups with 8 mice per group; animals were given in group 1 (non-diabetic control) and group 2 (diabetic control) fed standard diet with water supply, while groups 3, 4 and 5 were fed standard diet and different concentrations 300, 400 and 500 mg / dl / day respectively of aqueous extract of stevia leaf powder for a period of three weeks. A significant reduction was found in blood sugar, cholesterol, total fat and equal levels of other blood traits in groups 3 and 4 compared to group 2. The results also showed that giving the aqueous extract of Stevia at a concentration of 300 and 400 mg/kg weight, the blood sugar level is statistically and directly reduced in all treated diabetes-induced groups of mice. It also led to a statistical reduction of cholesterol and triglyceride. There is also a statistically significant increase in other blood characters in diabetic mice was also found that leaves of the stevia plant contained 7,86, 5,28 and 2,58% for both steviol glycoside, stevioside and rebaudoside respectively that measured by HPLC technique. These results have shown that consumption the leaves extract of stevia plant have an important role in reduction blood sugar, cholesterol and total fat, as well as other blood traits in mice induced for diabetes.